Peran dan Kendala Jurnalis Dalam Pemberitaan Deforestasi Di Aceh - Syukri Syamaun (Ar-Raniry State Islamic University, Indonesia, 2021)
This illegal logging practice occurs in almost all districts in Aceh. The mass media should be part of the socialization of various illegal logging cases that have occurred in Aceh. News Serambi Indonesia is able to carry out an in-depth and comprehensive investigation of illegal logging in Aceh. Serambi Indonesia must be able to expose the involvement of the